(4x-23)=(3x+17)

Simple and best practice solution for (4x-23)=(3x+17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-23)=(3x+17) equation:



(4x-23)=(3x+17)
We move all terms to the left:
(4x-23)-((3x+17))=0
We get rid of parentheses
4x-((3x+17))-23=0
We calculate terms in parentheses: -((3x+17)), so:
(3x+17)
We get rid of parentheses
3x+17
Back to the equation:
-(3x+17)
We get rid of parentheses
4x-3x-17-23=0
We add all the numbers together, and all the variables
x-40=0
We move all terms containing x to the left, all other terms to the right
x=40

See similar equations:

| 2y=5=13 | | 8t-7=3t+38 | | -12x+2x-74=166 | | 3x+44=86 | | 71=6s-9+s+3 | | -160=8a | | M+3/3=5,2m+2= | | -18-4x+5x=15 | | 628=2x-124 | | 28=14+6w | | 4^(x+1)=11 | | 5r+6+2r-11=37 | | w=2(w+24) | | -9x+4x-124=41 | | (5y+16)=34 | | 5r+62r-11=36 | | z=2(z-49) | | 87+x=122 | | -99-6x+11x=56 | | 10q-15-q=84 | | (6x-8)=(4x+6) | | 2z-49=z | | 1y+10=2y | | 2x+60=118 | | -101-12x-2x=179 | | 5p+13+3p=77 | | 2x-2=411 | | 27=10x+10 | | -8*x+17=-15 | | 2x8=1 | | 2x+2=411 | | -3x-5x-107=69 |

Equations solver categories